2022
DOI: 10.5603/fm.a2021.0029
|View full text |Cite
|
Sign up to set email alerts
|

The influence of mandibular divergence on facial soft tissue thickness in class I patients: a cephalometric study

Abstract: This article has been peer reviewed and published immediately upon acceptance.It is an open access article, which means that it can be downloaded, printed, and distributed freely, provided the work is properly cited. Articles in "Folia Morphologica" are listed in PubMed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 14 publications
0
4
0
1
Order By: Relevance
“…However, the statistically significant association only exists in women [ 37 ]. Likewise, Perovic et al have shown that upper lip thickness did not significantly differ dependently on vertical skeletal patterns, and that gender difference was established in this area [ 6 ]. Consistently in our study, upper lip thickness was not significantly different in three vertical skeletal pattern groups even after adjustment of all considered covariates including gender, indicating that the change in upper lip thickness was not dependent on vertical skeletal patterns.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the statistically significant association only exists in women [ 37 ]. Likewise, Perovic et al have shown that upper lip thickness did not significantly differ dependently on vertical skeletal patterns, and that gender difference was established in this area [ 6 ]. Consistently in our study, upper lip thickness was not significantly different in three vertical skeletal pattern groups even after adjustment of all considered covariates including gender, indicating that the change in upper lip thickness was not dependent on vertical skeletal patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple variates have been proven to influence soft tissue morphology. Gender is one of the most often-mentioned variates, with multiple studies showing that male patients tend to have thicker soft tissue compared with females with the same skeletal patterns, but the significance of gender difference varies among different skeletal patterns [ 6 , 10 , 38 ]. Race, as abovementioned, is an important genetic factor influencing soft tissue responding to skeletal patterns [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Эстетика лица -один из важнейших факторов, который необходимо учитывать при ортодонтическом лечении [12]. Известно, что нарушение окклюзии зубов приводит к изменениям контура мягких тканях лица [16]. Кроме того, зубы оказывают влияние на развитие скелета головы [15].…”
Section: Introductionunclassified